AN ANALYSIS DEIXIS OF PRESIDENT BARACK OBAMA’S FAREWELL ADDRESS IN NBC NEWS - Nouval, Moh. Javier Arifian; Utama, Insan Aji; Abdillah, Muhammad Ilham; Mahendra, Dzulfiqar Faisa; Salsabila, Salma; Laila, Malikstul (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2024)
This research discusses the deixis that appeared in President Barack Obama's farewell speech on NBC News on January 10, 2017 in Chicago. The Farewell Address focused on key themes such as democracy, unity, and the importance of civic engagement. The speech reflects his enduring belief in the fundamental values that define the United States and his hope for a better future for all Americans. To achieve the purpose of Obama's speech, the researcher used a deixis approach. The method used in this study is a qualitative descriptive method by recording all the data that appears in President Barack Obama’s Farewell Address in NBC News. Deixis can be used to influence audiences or readers in a variety of ways, including in order to establish identity, build emotional connections, or influence views and attitudes. The results of the study show that Obama often uses the word "we" because Obama wants his audience to receive information and influence Americans with his words. The most dominant spatial data that appears is America.